Long non-coding RNAs and circular RNAs in tumor angiogenesis: From mechanisms to clinical significance - Chen-Guang Liu; Juan Li; Yanhua Xu; Wan Li; Shu-Xian Fang; Qing Zhang; Hong-Wu Xin; Zhaowu Ma (Molecular Therapy: Oncolytics, 2021)
Long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) execute a wide array of functions in physiological and pathological processes, including tumor progression. Angiogenesis, an elaborate multistep process driving new blood vessel formation, accelerates cancer progression by supplying nutrients and energy. Dysregulated lncRNAs and circRNAs can reportedly impact cancer progression by influencing angiogenesis. However, the expanding landscape of lncRNAs and circRNAs in tumor progression-dependent angiogenesis remains largely unknown. This review summarizes the major functions of angiogenic lncRNAs (Angio-LncRs) and angiogenic circRNAs (termed Angio-CircRs) and their cancer mechanisms. Moreover, we highlight the commonalities of lncRNAs and circRNAs in epigenetic, transcriptional, and post-transcriptional regulation as well as illustrate how Angio-LncRs and Angio-CircRs induce cancer onset and progression. We also discuss their potential clinical applications in diagnosis, prognosis, and anti-angiogenic therapies.